2009
DOI: 10.1248/bpb.32.190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selenium Deficiency on Aldehyde Oxidase 1 in Rats

Abstract: Aldehyde oxidase 1 (AOX1, EC 1.2.3.1) and xanthine oxidase are major members of the molybdo-flavoenzyme family. Both enzymes consist of a homodimer with a subunit molecular mass of about 150 kDa. AOX1 catalyzes the oxidation of a wide range of endogenous and exogenous aldehydes and N-heterocyclic aromatic compounds. [1][2][3] The representative N-heterocyclic-containing drugs that serve as substrates for AOX1 are famciclovir, 4) methotrexate, 5) 6-mercaptopurine, 6) and cinchona alkaloids. 7) In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…SOD, GSH-Px, and GSH play important roles during the process by scavenging reactive oxygen species or by preventing their formation (Kabuto et al, 2003). GSH-Px is Se dependent and the deficiency of Se can lead to significantly reduced GSH-Px activity in rats (Itoh et al, 2009;Markiewicz-Górka et al, 2011). This relationship was also observed in this research.…”
Section: Discussionsupporting
confidence: 78%
“…SOD, GSH-Px, and GSH play important roles during the process by scavenging reactive oxygen species or by preventing their formation (Kabuto et al, 2003). GSH-Px is Se dependent and the deficiency of Se can lead to significantly reduced GSH-Px activity in rats (Itoh et al, 2009;Markiewicz-Górka et al, 2011). This relationship was also observed in this research.…”
Section: Discussionsupporting
confidence: 78%
“…Notably, there was no significant alteration of AOX mRNA levels after NIM treatment. The inconsistency between the mRNA level of AOX and the corresponding protein level and activity has been reported by a few studies [ 13 , 30 32 ]. The studies by Calzi et al showed that a correlation between AOX mRNA and protein levels in various tissues was not always evident, suggesting that both transcriptional and translational events controlled the expression of AOX [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Freshly prepared solutions of catechol estrogens were used for each experiment. Rat liver microsomal fraction (Four weeks old, male, Wistar strain, 20 mg protein/ml) used in this study was prepared [21] and donated by Dr. Yorihisa Tanaka (Department of Drug Metabolism and Pharmacokinetics, Tohoku Pharmaceutical University).…”
Section: Materials and Reagentsmentioning
confidence: 99%